2013
DOI: 10.1016/j.bbapap.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome bd-I in Escherichia coli is less sensitive than cytochromes bd-II or bo′' to inhibition by the carbon monoxide-releasing molecule, CORM-3

Abstract: Background: CO-releasing molecules (CO-RMs) are potential therapeutic agents, able to deliver CO – a critical gasotransmitter – in biological environments. CO-RMs are also effective antimicrobial agents; although the mechanisms of action are poorly defined, haem-containing terminal oxidases are primary targets. Nevertheless, it is clear from several studies that the effects of CO-RMs on biological systems are frequently not adequately explained by the release of CO: CO-RMs are generally more potent inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 72 publications
4
42
1
2
Order By: Relevance
“…The rationale for the latter observation could be that, based on the available literature, beyond its role in cell bioenergetics, cytochrome bd seems to accomplish several important physiological functions that enable bacterial survival in different ecological niches and, importantly, resistance to the hostile conditions created by the immune system in response to microbial infections (reviewed in [14,41,42]). In agreement with this hypothesis, there is growing evidence in the literature pointing to a protective role of cytochrome bd against a number of stressors, including H 2 O 2 [23,[42][43][44][45][46][47][48][49][50][51][52], NO• [41,[53][54][55][56][57][58], CO [59], nitrite [60,61] and excess O 2 itself [62]. Intriguingly, all these species are implicated in the host immune response against microbial infections.…”
Section: Introductionmentioning
confidence: 68%
“…The rationale for the latter observation could be that, based on the available literature, beyond its role in cell bioenergetics, cytochrome bd seems to accomplish several important physiological functions that enable bacterial survival in different ecological niches and, importantly, resistance to the hostile conditions created by the immune system in response to microbial infections (reviewed in [14,41,42]). In agreement with this hypothesis, there is growing evidence in the literature pointing to a protective role of cytochrome bd against a number of stressors, including H 2 O 2 [23,[42][43][44][45][46][47][48][49][50][51][52], NO• [41,[53][54][55][56][57][58], CO [59], nitrite [60,61] and excess O 2 itself [62]. Intriguingly, all these species are implicated in the host immune response against microbial infections.…”
Section: Introductionmentioning
confidence: 68%
“…Subsequent time-resolved analysis revealed that the transcription of appBC , which encodes cytochrome bd -II is not affected in response to CORM-3 [81]. In support, a strain expressing cytochrome bd -I as the sole oxidase is less susceptible to both respiratory and growth inhibition by this compound [82], consistent with the established role of this oxidase in resisting a variety of environmental stresses including NO [83]. In the case of NO, it has been proposed that cytochrome bd resists inhibition because of an exceptionally high off rate ( k off 0.163 s −1 for cytochrome bd , compared to 0.03 s −1 for cytochrome bo' [83]), although it is difficult to draw such conclusions for CO due to discrepancies in the literature as to the off rate of this gas from cytochrome bd -I (see references in [82]).…”
Section: Carbon Monoxide – the New No?mentioning
confidence: 99%
“…bactericidal activity of CO-RMs is reduced by the presence of a number of molecules, including N-acetylcysteine, cysteine and reduced glutathione (Desmard et al, 2009;Jesse et al, 2013;McLean et al, 2013), and so is likely to be diminished in a complex medium such as LB. The reasons are unclear.…”
Section: Discussionmentioning
confidence: 99%